ESP32-based IoT system for controlling and monitoring greenhouse crops with an agriculture 4.0 approach - Berrios Gomez, Sebastian (2022)
Agriculture 4.0 incorporates information and communication technologies such as the Internet of Things (IoT), databases and smartphone applications. Greenhouse farming, at the same time, allows a rational use of water resources and a greater production in smaller cultivation areas. The increase in productivity generates the right conditions to ensure the nourishment of populations in the near future. The research presents a proposal for an IoT system to monitor and control parameters inherent to greenhouse crops based on the ESP32 microcontroller, using sensor nodes to collect data on temperature, relative humidity, soil moisture, as well as water level for irrigation. Using the ESP-NOW wireless communication protocol, the sensor nodes send the information to the central node. The central node activates and deactivates the actuators to control the climatic parameters and saves the information in a database for real-time monitoring. The mobile application displays readings from the database and allows actuators to be turned on and off manually. The system was developed for growing lettuce in tunnel greenhouses, but can be applied to other types of crops and greenhouses due to its flexibility.